"What Are You?" Conceptualizing the Complexities of Bicultural and Biracial College Student Experiences. Issue 2 (6th July 2019) - West, Michael T.; Maffini, Cara S.
Abstract : Reflecting the increasing diversity of the United States, universities are seeing growing rates of students from diverse cultural backgrounds. The authors present culturally responsive suggestions to facilitate conceptualization and counseling with biracial and bicultural college students, integrating cognitions, behaviors, emotions, and relationships associated with culture and cultural identity of both culture of origin and mainstream U.S. culture. Recommendations for counseling an increasingly diverse student body are presented.